Construction method of quantitative evaluation model for the maturity of Korla fragrant pear - Yu, Shihui; Tang, Yurong; Lan, Haipeng; Li, Xiaolong; Zhang, Hong; Zeng, Yong; Niu, Hao; Jin, Xiaozhen; Liu, Yang (International Journal of Agricultural and Biological Engineering, 2022)
The maturity variation laws of Korla fragrant pears were explored for a quantitative evaluation of harvest maturity to solve the reasonable matching between harvest maturity of Korla fragrant pears and market quality demands. Korla fragrant pears from different harvesting periods were chosen as the research objects. Some quality indexes were chosen as the evaluation indexes per industry standards, including hardness, soluble solid content (SSC), single-fruit weight, fruit longitudinal diameter, fruit equatorial diameter, pericarp color parameters (L*, a*, and b*), and titratable acid. Variation data of these quality indexes with accumulated temperature were collected. Scores of several quality indexes were gained through principal component analysis. A mathematical model of scores and accumulated temperatures was constructed. On this basis, a quantitative maturity model of Korla fragrant pears was constructed. Results demonstrate that SSC, single-fruit weight, fruit longitudinal diameter, fruit equatorial diameter, L*, a*, and b* are significantly and positively correlated with the accumulated temperature. Meanwhile, hardness and titratable acid showed significant negative correlations with the accumulated temperature. Relations between scores of principal components and accumulated temperature conform to the Sigmoidal model. The constructed quantitative maturity model of Korla fragrant pears can quantify the maturity of pears. Research conclusions can provide insight into the harvest periods, evaluate Korla fragrant pears’ maturity, and lay a theoretical foundation for quantitative research on fruit maturity.Keywords: Korla fragrant pear, quantitative evaluation, maturity, principal component analysis, model constructionDOI: 10.25165/j.ijabe.20221504.6653Citation: Yu S H, Tang Y R, Lan H P, Li X L, Zhang H, Zeng Y, et al. Construction method of quantitative evaluation model for maturity of Korla fragrant pear. Int J Agric & Biol Eng, 2022; 15(4): 243–250.